A53 STUDYING THE ROLE OF ASCL2 IN THE ESOPHAGEAL EPITHELIUM USING ORGANOIDS. (4th March 2021) - Hamilton, M; Jean, D; Giroux, V
Abstract: Background: The esophagus is lined with a stratified squamous epithelium that assure protection against the austere environment found in the esophageal lumen. The maintenance of this epithelium is ensured by a rare population of cells: stem cells. Those cells have increased capacity of self-renewal and multipotency, which is the capacity to give rise to every cell types of a tissue. The marker Krt15 was used to identify the first stem cell population in the esophagus. Krt15+ cells display an extended lifespan and they are radioresistant, multipotent and capable of self-renewal. Moreover, it was observed by RNA sequencing that the expression of the transcription factor ASCL2 is strongly increased in Krt15+ cells compared to Krt15 - cells. Interestingly, ASCL2 is necessary to maintain the stemness of Lgr5+ intestinal stem cells. It is also a target of the Wnt/β-catenin pathway. The overall goal of this project is to determine the role of ACSL2 in the maintenance of esophageal stem cells and to identify its binding partners since ASCL2 needs to dimerize to efficiently bind DNA. Aims: Confirm that esophageal organoids are adapted to study ASCL2 in the esophagus. Methods: Esophageal organoids were established from esophageal epithelial cells from wildtype mice. Following this, organoids were treated with an inhibitor of the Notch pathway (DAPT) to induce hyperplasia or infected with lentiviruses to invalidate Ascl2 (CRISPR/Cas9 approach). Results: To validate that Ascl2 plays an important role in esophageal cell proliferation, Notch pathway was inhibited through DAPT treatment in esophageal organoids to induce hyperplasia, which was confirmed by increased number of proliferative cells (Ki-67+). ASCL2 protein expression was also increased in DAPT-treated organoids supporting its role in proliferation and confirming that organoid is a good model to study ASCL2 role in esophageal epithelial cells. In this optic, organoids lines invalidated for Ascl2 (CRISPR/Cas9 approach) were established. Our preliminary results suggest that Ascl2 loss affects cell proliferation and organoid size under normal conditions. Conclusions: The expression of ASCL2 correlates with hyperplasia which supports its role in esophageal epithelium homeostasis. Funding Agencies: Canada research chair et NSERC